Two Higgs-doublet models in future e−p colliders - Mosomane, Chuene Johannes (My University, 2018)
We review the general two Higgs doublet model and its particle spectrum. This model has four types, which are Type-I, Type-II, Type-X (lepton specific) and Type-Y (Flipped). We discuss the Madala hypothesis as a Type-II two Higgs doublet model, where the Madala hypothesis introduces the Madala boson (which is a doublet-like heavy Higgs boson) with mH = 270 GeV. We study the Madala boson in the proposed LHeC, which is a ep collider. The Madala boson has a higher crosssection in the LHeC with proton beam energy of Ep = 7 TeV in the charge current and the neutral current is suppressed.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Science in the School of Physics, Johannesburg, 2016.
Keywords: Large Hadron Collider (France and Switzerland); Particles (Nuclear physics)